Moderating Effect of Mental Health on the Association between Teachers ’ Stress and their Professional Attitude in Tanzania - Masath, Faustine Bwire (Papers in Education and Development, 2023)
Various reports show that there is an increase in teachers ' stress and a decline in teachers ' professional attitude in Tanzania. Few studies have examined the reasons for such situation. This study examined the moderating effect of mental health on the association between teachers ' level of stress and their professional attitude. The study used a selected sample of teachers from 12 randomly selected public primary schools of Tanzania (N = 173, Mean Age = 38.10 years, SD = 10.0). Using hierarchical regression moderation model, a significant association was found between teachers ' professional attitude and their level of stress (Î² = €“ .21, p < .001), which was moderated by mental health (Î² = €“ .12, p < .029). The findings call for interventions to enhance teachers ' wellbeing including the wellbeing of their mental health in order to improve their organizational and life performance in the country. Keywords: mental health, professional attitude, teachers ' stress, Tanzania